The Incidence of Misdiagnosis in Patients with Ehlers–Danlos Syndrome - Chanbin Lee; Pradeep Chopra (Children, 2025)
Background: Misdiagnosis, defined as the incorrect identification of a condition or the failure to identify a condition altogether, can lead to delayed treatment, unnecessary interventions, and avoidable morbidity and mortality. Ehlers–Danlos Syndrome (EDS) is a complex pain disorder that is often misdiagnosed or underdiagnosed due to lack of awareness among healthcare providers and variability in diagnostic criteria. Objectives: This study aimed to determine the misdiagnosis rate of hypermobile EDS (hEDS) with psychiatric disorders by physicians who are not board-certified in psychiatry. Methods: Between January 2010 and December 2018, the medical records of 429 patients who were diagnosed with hEDS were reviewed and analyzed. During the process of taking a history, patients were asked if they had previously been told by physicians who were not board-certified in psychiatry that their symptoms were “in their head”, that they were “making it up” or seeking attention, or that they might suffer from Munchausen syndrome by proxy or a factitious disorder, or if such physicians had diagnosed them with conversion disorder. The Brown University Human Research Protection Program determined that the proposed activity was not research involving human subjects. Results: A retrospective chart review was conducted. Among the 429 patients, 405 patients (94.4%) said yes to at least one of the questions, with only 24 patients (5.6%) not having been misdiagnosed with psychiatric illnesses. A total of 378 patients (88%) were told that they were “making it up”, 326 patients (76%) were told that they were attention-seeking, 286 patients (67%) were diagnosed with conversion disorder, 255 patients (60%) were told that “it was in their head”, and 16 patients (4%) were diagnosed with Munchausen syndrome by proxy or a factitious disorder. Conclusions: Misdiagnosis of Ehlers–Danlos Syndrome is a pervasive issue with profound implications for patients’ physical, mental, and economic well-being. By addressing the underlying causes of misdiagnosis and implementing strategies for improved recognition, the healthcare system can significantly enhance outcomes for individuals who are affected by these complex disorders.